Online Learning and Teaching using Google Classroom during the COVID 19 Pandemic - Sharda, Preeti; Bajpai, Maneesh Kumar (DESIDOC Journal of Library & Information Technology, 2021)
The ‘Google Classroom’ is one of the technologies used for the teaching and learning process. This paper explores the possibilities of how Google Classroom may be brought into use by educators for the effective teaching-learning process. The study’s main objectives are to understand ‘Google Classroom’ technology and find out the use of Google Classroom by the educators of India particularly during the COVID-19 pandemic situation. The study is quantitative research in nature. The data collected through Google form contains 18 questions. A sample of 1050 educators was collected to know the usage of Google classroom in the teaching-learning process. The result indicated that most of the respondents are using Google Classroom for teaching purposes which is good in terms of Ease of access, perceived usefulness, tracking the progress of students, communication and interaction between the teachers and the students. Results also show the effective use of google classroom by the librarians to provide e-library services to their users when physical access to libraries is not available. The study recommends that the Google Classroom may be used to enhance quality in imparting teaching and learning activities at all levels of education, especially during the Pandemic.